Analisis Potensi Bahaya (Unsafe Action & Unsafe Condition)Dan Pengendalian Risiko Di Proyek Konstruksi Manggarai “Main Line 1” Phase II Nindya Citra Kharisma KSO Jakarta Selatan - Siska Melati; Herlina Herlina (STIKes Persada Husada Indonesia, 2021)
The development of the construction service industry has progressed, there are many hazards that workers can encounter in the workplace.The existence of this hazard can lead to accidents, so the implementation of the K3 program is a must for companies, especially Nindya Citra Kharisma KSO.This study aims to determine the analysis of potential hazards (unsafe action & unsafe condition) and risk control in the Manggarai